Characterisation of ethylene flames under a range of low-oxygen concentrations. (15th February 2023) - Shaw, Ian J.; Evans, Michael J.; Chin, Rey; Medwell, Paul R.
Abstract: New understanding of turbulent ethylene (C2 H4 ) jet flames, issuing into a range of preheated coflowing oxidisers with reduced oxygen (O2 ) concentrations are reported. These conditions emulate moderate or intense low-oxygen dilution (MILD) combustion. To resolve previously reported non-monotonic trends, comparisons are made for coflow O2 concentrations of 3 %, 4 %, 5 %, 6 %, 9 % and 11 % and coflow temperatures of 1250 K, 1315 K and 1385 K. Instantaneous and simultaneously planar imaging measurements of temperature, hydroxyl radicals (OH) and formaldehyde (CH2 O) were taken at eight downstream locations ranging from 9 mm to 75 mm. The new data reveal non-monotonic lift-off trends in the OH and CH2 O formation heights at all three temperatures. Compared with extant measurements, the higher resolution and greater control of coflow composition provide a detailed exploration of the transitional behaviour that occurs when MILD combustion conditions are achieved. The results experimentally demonstrate non-monotonic variation in lift-off height, and show that the same behaviour is present in both the OH and CH2 O formation heights, and occurs at all three temperatures, which is due to the movement of the location of the stoichiometric and most reactive mixture fractions to the coflow side of the jet shear layer. The results also show that increasing the oxidiser temperature does not have a significant effect on the OH number density for a given temperature but does result in a significant decrease in lift-off height and CH2 O concentration. Highlights: OH and CH2 O in C2 H4 flames have non-monotonic behaviours with oxidiser O2 . Behaviour indicates transition from hot-and-vitiated combustion to MILD combustion. Range at which this transition occurs narrowed to 4–5 % O2 . CH2 O concentration varies with oxidiser concentration peaking at 6% O2 . CH2 O variation which may indicate reaction zone weakening in low O2 conditions.